Delaying the implementation of Payment by Results in mental health: the application of standardisation - Shaw, Ian (Emerald, 2015)
Purpose – The purpose of this paper is to explore the issues surrounding a long planned expansion of Payment by Results (PbR) into mental health services and to highlight the factors responsible for the delay.